Intradermal DNA Electroporation Induces Cellular and Humoral Immune Response and Confers Protection against HER2/neu Tumor - Alessia Lamolinara; Lorenzo Stramucci; Albana Hysi; Manuela Iezzi; Cristina Marchini; Marianna Mariotti; Augusto Amici; Claudia Curcio (Journal of Immunology Research)
Skin represents an attractive target for DNA vaccine delivery because of its natural richness in APCs, whose targeting may potentiate the effect of vaccination. Nevertheless, intramuscular electroporation is the most common delivery method for ECTM vaccination. In this study we assessed whether intradermal administration could deliver the vaccine into different cell types and we analyzed the evolution of tissue infiltrate elicited by the vaccination protocol. Intradermal electroporation (EP) vaccination resulted in transfection of different skin layers, as well as mononuclear cells. Additionally, we observed a marked recruitment of reactive infiltrates mainly 6–24 hours after treatment and inflammatory cells included CD11c+. Moreover, we tested the efficacy of intradermal vaccination against Her2/neu antigen in cellular and humoral response induction and consequent protection from a Her2/neu tumor challenge in Her2/neu nontolerant and tolerant mice. A significant delay in transplantable tumor onset was observed in both BALB/c (p≤0,0003) and BALB-neuT mice (p=0,003). Moreover, BALB-neuT mice displayed slow tumor growth as compared to control group (p<0,0016). In addition, while in vivo cytotoxic response was observed only in BALB/c mice, a significant antibody response was achieved in both mouse models. Our results identify intradermal EP vaccination as a promising method for delivering Her2/neu DNA vaccine.